Are there sensitive periods for skill development in male adolescent basketball players? - Guimarães, E.; Baxter-Jones, A. D. G.; Williams, A. M.; Anderson, D. I.; Janeira, M. A.; Garbeloto, F.; Pereira, S.; Maia, J. (Medicine & Science in Sports & Exercise, 2024)
Purpose Although spurts in physical capacities during adolescence are well-known, little is known about the existence of such spurts in sport-specific skill development, especially during the period of rapid growth in stature. Our aims were to examine the timing, intensity, and sequence of basketball-specific skill spurts aligned with biological [years from peak height velocity (PHV)] rather than chronological age. We then defined putative sensitive periods (windows of optimal development) for each skill aligned to the adolescent growth spurt.